Awareness of Dental students about tobacco in Teaching Hospital: A cross sectional study - garg, Deepanshu (Journal of College of Medical Sciences-Nepal, 2018)
ABSTRACT Background:One of the leading causes of disability and premature deaths all over the globe is tobacco. By starting tobacco cessation programs in their daily practices, dentists can play an important role by giving opportunity of a healthy lifestyle to the people. The aim of this study was to check the knowledge of BDS students regarding consequences and risk factors of tobacco. Materials and Methods:This cross sectional study was conducted among the dental students of College of Medical Sciences and Teaching Hospital to evaluate the level of awareness about tobacco and its side effects. A total of 150 students were enrolled in the study who were distributed a questionnaire which consisted of relevant questions regarding the knowledge of tobacco. Results:The results of the study concluded that 76% of the students were aware about the ill effects of smoking or chewing tobacco on health. 71% of the total students enrolled chose to be non-smokers in future. Conclusion:The present study concludes that tobacco cessation program should be included in the curriculum of dental students so that they get proper training in imparting the valuable information to the general public. Keywords: awareness; cessation; dental; students; tobacco.